Performance Analysis of Islamic Religion Teachers According to Standards Competencyat Elementary Schools and Madrasah Ibtidaiyah in Cilongok District, Banyumas Regency - Imam Hidayat (Islamic Studies Journal, 2022)
The purpose of this study was to analyze the performance and competency standards of Islamic Religion Teachers at Elementary Schools and Islamic Elementary Schools in Cilongok District, Banyumas Regency. The population of this study were all Islamic Religion teachers at MI in Cilongok District, Banyumas Regency, totaling 46 teachers. The sample in this study were 46 people. Sampling was done by total sampling method. Data was collected through a questionnaire. The data analysis includes descriptive analysis, prerequisite test consisting of normality test, linearity test, and multicollinearity test, and multiple regression analysis with F test, t test, and determination test. The results showed that there was a significant positive contribution of the principal's managerial skills, work discipline, and compensation for teacher performance at MI in Dlingo, Bantul Regency.